Estimating the size and incidence of bank resolution costs for selected banks in OECD countries - Blix Grimaldi, Marianna (OECD Publishing, 2016)
This report provides estimates of the costs associated with bank resolution both in terms of the expected costs that might arise should a bank fail (i.e. as "ex-post" costs), as well as the cost associated with the likelihood that a solvent bank might fail (i.e. as "ex-ante" costs) over the next year. It finds that expected resolution costs (ex-post costs) have dropped recently due to higher average capital ratios and a lower level of bank liabilities as a percentage of GDP. The annualised value of these expected resolution costs (ex-ante costs), which increased sharply after 2008, has since subsided, but remains well above its 2008 level. Overall, the estimates produced in this report support the notion that recent financial sector reforms have had an impact on reducing the costs associated with bank failure, including the expected costs to taxpayers. However, estimates are in most cases yet to return to pre-crisis levels
Keywords: Finance and Investment